Assessing methyl tertiary butyl ether residual contamination in groundwater using radon. (May 2020) - Briganti, Alessandra; Tuccimei, Paola; Voltaggio, Mario; Carusi, Claudio; Galli, Gianfranco; Lucchetti, Carlo
Abstract: About 15 years ago, a fuelling station in Roma (Italy) was dismissed. When underground tanks were removed, a subsoil NAPL (Non-Aqueous Phase Liquid) contamination came out, showing gasoline leakage from the reservoirs. Monitoring actions took place next and only recently radon dissolved in groundwater was measured for a year and used as tracer of NAPLs in view of its high solubility in these substances. The relative deficit of radon in polluted groundwater compared to radon in background "clean" water allowed us to detect areas where residual gasoline is still located. The source of pollution was identified in correspondence of former gasoline tanks, in agreement with direct measurements of dissolved NAPLs, mainly Methyl Tertiary Butyl Ether (MTBE), a resistant and water-soluble additive introduced in gasoline in place of lead. A short and transient plume of MTBE was occasionally recognized. We hypothesize that the rise of groundwater table enhances removal of MTBE, likely adsorbed onto soil minerals such as zeolites, thus increasing its concentration in water. MTBE levels are then progressively reduced by natural attenuation processes, with half-life of about 23 days. Estimates of MTBE saturation from radon-deficit equations were not reliable because the aquifer is not homogeneous in terms of 226 Ra distribution, porosity and emanation power and no equilibrium is reached for radon partitioning between NAPL and water. Highlights: In 2004 a fueling station was dismissed and a subsoil contamination appeared. Radon-deficit in MTBE-contaminated groundwater allowed to identify residual NAPLs. The source of pollution was documented in correspondence of former gasoline tanks. A transient plume, mobilized by the rising water table, was occasionally recognized. MTBE levels are reduced by natural attenuation processes, with half-life of 23 days.